Division of Marital Property in Divorce Due to Domestic Violence: A Gender Justice Perspective - Abd. Basit Misbachul Fitri (STAI Miftahul Ula Nganjuk, 2026)
The intersection of marital property division and domestic violence in Indonesian divorce proceedings reveals a profound gender justice deficit that existing family law frameworks have failed to adequately address. This study employs a normative-empirical legal research methodology to systematically examine whether the current legal regime governing marital property (harta bersama) division—under the Marriage Law Number 1 of 1974 as amended by Law Number 16 of 2019, the Compilation of Islamic Law (KHI), and Law Number 23 of 2004 on the Elimination of Domestic Violence (UUPKDRT)—sufficiently incorporates gender justice principles in cases where divorce is precipitated by domestic violence. Drawing on an analysis of selected court decisions from religious courts (Pengadilan Agama) and district courts (Pengadilan Negeri) from 2018 to 2023, supplemented by data from the National Commission on Violence Against Women (Komnas Perempuan), this study identifies a systematic pattern of gender injustice: courts consistently apply a formal equality standard in marital property division regardless of the history of domestic violence, thereby failing to account for the economic coercion, loss of earning capacity, and disproportionate unpaid labor contributions that characterize the economic experience of domestic violence survivors. Comparative analysis with Australia's Family Law Act and South Africa's Recognition of Customary Marriages Act illuminates viable reform pathways. The study proposes a gender-responsive marital property division framework that incorporates domestic violence as a factor requiring upward adjustment of the survivor's share, economic compensation for caregiving contributions, and procedural protections for survivors navigating property division proceedings.